Efektivitas Penyuluhan Kesehatan melalui Teknologi Digital terhadap Pengetahuan Ibu tentang Pencegahan Stunting di Desa Bojong - Annisa Syafa Nursabilla; Indra Tri Astuti; Nopi Nur Khasanah (Jurnal Siti Rufaidah, 2025)
The 2022 SSGI data show that 20.8% of children under five in Central Java experience stunting, with the highest prevalence found in Brebes Regency at 29.1%. Mothers play a crucial role in preventing stunting among children. Health education utilizing digital technology is one of the strategies that can be applied to address this issue. This study aimed to determine the effectiveness of digital technology–based health education on improving mothers’ knowledge regarding stunting prevention in Bojong Village, Brebes Regency. A quasi-experimental design with a pre–post test control group was employed, involving 42 respondents divided into an experimental group (education through video followed by WhatsApp Group follow-up) and a control group (oral education). The results showed a significant increase in knowledge scores in both groups (p<0.05), from 2.71 to 9.9 in the experimental group and from 3.76 to 7.76 in the control group. It can be concluded that nutritional education delivered through both digital media and oral communication is equally effective in improving mothers’ knowledge about stunting prevention.